A Multicenter, Prospective, Noninterventional Study in a Norwegian Cohort of Patients with Moderate-to-Severe Allergic Rhinitis Treated with MP-AzeFlu. Issue 3 (October 2017) - Dollner, Ralph; Larsen, Petter Lorentz; Dheyauldeen, Sinan; Steinsvåg, Sverre
Background: Allergic Rhinitis and its Impact on Asthma guidelines recently recommended a treatment strategy for allergic rhinitis (AR) based on disease control rather than symptom severity by using a visual analog scale (VAS) to categorize control Objectives: To evaluate the effectiveness of MP-AzeFlu (Dymista ® ) by using this VAS in routine clinical practice in Norway. MP-AzeFlu comprises a novel formulation that contains azelastine hydrochloride, fluticasone propionate and excipients delivered in a single spray. Methods: This multicenter, prospective, noninterventional study enrolled patients (n = 160) with moderate-to-severe AR and acute symptoms who were eligible to receive treatment with MP-AzeFlu according to its summary of product characteristics. Patients assessed symptom severity by using a VAS from 0 (not at all bothersome) to 100 mm (very bothersome) in the morning before MP-AzeFlu use on days 0, 1, 3, 7, and after ~14 days. On day 3, the patients assessed their level of disease control as well controlled, partly controlled, or uncontrolled. The proportion of Norwegian patients who achieved defined VAS score cutoffs for "well-controlled" and "partly controlled" AR were also calculated. Results: MP-AzeFlu reduced the mean ± standard deviation VAS score from 68.1 ± 16.4 mm at baseline to 37.4 ± 25.9 mm on the last day, a reduction of 30.8 ± 27.2 mm. The results were consistent, irrespective of disease severity, phenotype (i.e., seasonal AR [SAR], perennial AR [PAR], SAR plus PAR, unknown) or age (i.e., 12–17, 18–65, and >65 years). Of the patients (with recorded data), 88.1% considered their symptoms to be partly or well controlled at day 3; and 19.5, 32.0, 50.0, and 61.0% of the patients achieved a ≤38 mm well-controlled VAS score cutoff on days 1, 3, 7, and the last day, respectively. Conclusions: MP-AzeFlu provided rapid sustained symptom control in a routine clinical practice in Norway, which provided support for its effectiveness for the treatment of AR in real life.